The effect of temperature and concentration on the corrosion inhibition mechanism of an amphiphilic amido-amine in CO2 saturated solution - Desimone, Paula Mariela (2011)
The corrosion inhibition mechanism of the N-[2-[(2-aminoethyl)amino]ethyl]-9-octadecenamide on mild steel surface in CO2-saturated 5% NaCl solution has been studied. The inhibition efficiency decreases with increasing temperature. Adsorption of the inhibitor studied is found to follow the Frumkin adsorption isotherm. EIS results show that the mechanism of its corrosion inhibition at concentrations higher than critical micelle concentration is by forming a protective porous bi-layer. The activation energy, thermodynamic parameters and electrochemical results reveal a change in the adsorption mode of the inhibitor studied: the inhibitor could primarily be physically adsorbed at low concentrations, while chemisorption is favoured as concentration increases.